Identify unmet needs in diabetes care in Shandong, China: a secondary analysis of a cross-sectional study using cascade of care framework - Yueqing Wang; Jie Ren; Xin Chai; Yachen Wang; Zilong Lu; Jing Dong; Xiaolei Guo; Xuejun Yin; Juan Zhang; Junli Tang; Jixiang Ma; Ruitai Shao (BMC Endocrine Disorders)
Abstract Background The continuum management of diabetes remains under-evaluated in China. This study aimed to estimate the proportions of diabetes adults at each stage of the cascade of care framework in Shandong, China. Methods We conducted a secondary analysis using the 2018 China Adult Chronic Disease and Nutrition Surveillance (CACDNS) data in Shandong. This nationwide cross-sectional survey was conducted between September and November 2018, investigating the major chronic diseases among Chinese adults through interviews, physical examinations, and laboratory tests. We employed the cascade model to examine the proportion of diabetes adults, including both type 1 and type 2, from diabetes screening, diagnosis, pharmaceutical and non-pharmaceutical treatments, to single and comprehensive management targets, and quantified the attrition between each stage. Diabetes screening was defined as participants reported to have ever received a blood glucose test. Diabetes diagnosis was defined as: 1) fasting plasma glucose (FPG) ≥ 126 mg/dL, or 2) 2-h oral glucose tolerance test (2 h-OGTT) ≥ 200 mg/dL, or 3) hemoglobin A1c (HbA1c) ≥ 6.5%, or 4) self-reported diabetes. Diabetes management targets included: 1) single glycemic target of personalized HbA1c level, 2) comprehensive ABC targets of personalized HbA1c level, blood pressure (BP) < 140/80 mm Hg, and low-density lipoprotein cholesterol (LDL-c) level < 2.6 mmol/L, 3) lifestyle target of not currently smoking. The estimated proportion was calculated through self-reported diabetes status and FPG, 2h-OGTT and HbA1c. The number of diabetes cases in Shandong was extrapolated using the 2018 provincial census data for adults aged 18 years and above (N = 80.6 million). The cascade of diabetes care was further examined by age, sex, and Basic Public Health Service (BPHS) enrollment. Results This secondary analysis included 8,462 individuals (47.8% males, median age: 49.0), among whom 12.4% had diabetes (self-reported: 4.2%, newly diagnosed: 8.2%) and 41.1% had prediabetes. In 2018, an estimated 9.2 million adults in Shandong had diabetes, with 6.4 million (69.6%) receiving diabetes screening but 6.2 million (67.7%) remaining unaware of their conditions. Among self-reported diabetes adults, 2.7 million (86.4%) and 2.8 million (89.6%) received pharmaceutical and non-pharmaceutical treatment, respectively. Of those with treatments, 1.2 million (58.2%) met personalized glycemic target. A rapid decline, however, was observed in BP (31.1%) and LDL-c (39.3%) control among diabetes patients with multimorbidity (≥ 2 diseases). Ultimately, 0.1 million self-reported diabetes adults (3.8%) achieved the ABC targets. BPHS Enrollment slightly improved comprehensive management with ABC targets. Conclusions A significant unmet need exists for diabetes adults from screening to management, particularly the comprehensive management of glycemia, BP and LDL-c levels among those with multimorbidity. Tailored strategies and appropriate allocation of healthcare resource is needed to addressing gaps in care continuum and reduce long-term disease burden.